Agroforestry Research at a Crossroads - Nair, P K.R (Annals of Arid Zone, 2016)
Organized research in agroforestry was initiated nearly 25 years ago. At that time, the expectations were high on the potential of agroforestry as a development vehicle and the role of research in realizing that potential. Many of these expectations remain largely unfulfilled. Although agroforestry is becoming a rigorous science, the research focus has mostly been on biophysical issues at plot or field level; social, economic, and policy issues, as well as broader-scale and long-term issues have received little attention. Furthermore, in many developing countries, agroforestry research is mainly of an observational and exploratory nature, with little emphasis on process-oriented investigations to understand the reasons of the observed behavior. Therefore, the results lack scientific rigor and reproducibility. In order to overcome this, it is essential that agroforestry research is re-evaluated and refocused. A matrix of temporal (short-, medium-, and long-term) objectives and spatial (local, regional, and global) focus is suggested as a guide for natural resource management in agroforestry research. The matrix could be applied at different levels and institutional hierarchies. Research agenda at the institutional levels should be broadened to include such items as agronomic components of agrofore;try, domestication of indigenous trees, development of appropriate research methodologies, socio-economic studies, ano impact assessment. Broader-scale research issues of a long-term nature should include carbon sequestration, environmental amelioration including water quality enhancement, and biodiversity conservation. Research strategies should eschew the dichotomy of the .. versus" syndrome (such as on-farm vs. on-station, socio-economic vs. biophysical, and local vs. global), and replace versus with and so that future research will involve a proper balance between on-farm and on-station studies on socio-economic and biophysical issues of local and global importance.